eta ->gamma gamma decay width via the Primakoff cross section - Rodrigues, T. E.; Arruda-Neto, J. D. T.; Mesa, J. [UNESP]; Garcia, C.; Shtejer, K.; Dale, D.; Nakagawa, I.; Cole, P. L. (Amer Physical Soc, 2008)
Incoherent eta photoproduction in nuclei is evaluated at forward angles within 4 to 9 GeV using a multiple scattering Monte Carlo cascade calculation with full eta-nucleus final-state interactions. The Primakoff, nuclear coherent and nuclear incoherent components of the cross sections fit remarkably well previous measurements for Be and Cu from Cornell, suggesting a destructive interference between the Coulomb and nuclear coherent amplitudes for Cu. The inelastic background of the data is consistently attributed to the nuclear incoherent part, which is clearly not isotropic as previously considered in Cornell's analysis. The respective Primakoff cross sections from Be and Cu give Gamma(eta ->gamma gamma)=0.476(62) keV, where the quoted error is only statistical. This result is consistent with the Particle Data Group average of 0.510(26) keV and in sharp contrast (similar to 50%) with the value of 0.324(46) keV obtained at Cornell.